COVID-19 re-infection or persistent infection in patient with Acute Myeloid Leukemia M3; A mini review (2020)
Up to now, COVID-19 pandemic affected more than 40 million of people worldwide. Some of the patients had episodes of symptoms recurrence after the first episode of infection with variable intervals. There are multiple issues and hypotheses about re-infection or re-activation of COVID-19 virus, especially in immunocompromised patients. In this paper first, we present a case with a recent history of COVID-19 infection who proceeded to Acute Myeloid Leukemia M3 and immunosuppression by chemotherapy, then we review some recently published articles about possible re-infection or reactivation.